SYMBOL AND ALLEGORY IN MODERN ENGLISH LITERATURE (Web of Teachers: Inderscience Research, 2024)
In literature symbolism is used to embody something more than itself. Symbols can vary from objects, people, situations, and actions or any other element with literal meaning.Without some type of emphasis, repition, or position in the work the reader may have little success identifying symbolic value. Allegory is a fancy word that really just means "extended metaphor." In an allegory, people, places, things, and happenings (oh, those nouns) have two layers of significance.